What to expect when mommy's having an baby - Murkoff, Heidi Eisenberg; Rader, Laura ([New York?] : HarperFestival, 2000)
Designed to help you answer your childs questions about how a baby is created, how it grows and how it comes out to join the family.
"Ages 2-5"--p. [4] of cover.
Keywords: Newborn infants; Sex instruction for children; Babies